Characterization of Bimetallic Interface in Cu–Al and Ni–Cu Rods Cold Welded by Equal Channel Angular Pressing. Issue 1 (13th December 2019) - Zhilyaev, Alexander P.; Werner, Thomas; Cabrera, Jose Maria
Abstract : While cold welding by equal channel angular pressing has already been confirmed to be a viable alternative to join materials that commonly tend to exhibit unwanted brittleness and other heat‐induced properties, the exact processes taking place at the interface as well as their effects have not been well studied. Herein, the exact chemical composition along the bimetal interface is analyzed by multiple energy‐dispersive X‐ray spectroscopy line scans. Furthermore, microhardness maps are drawn up based on Vickers microindentations in the same area. Based on these findings, the presence and distribution of intermetallics, as signs of successful welding, are determined, as well as their influence on the mechanical properties of the weld. Abstract : The welding of Cu–Al and Ni–Cu systems is performed using equal channel angular pressing (route C) at room and elevated temperature. It leads to the formation of intermetallic particles and solid solution. However, unlike conventional welding, these hard and brittle particles do not lower the mechanical properties of the weld.